Evaluating the halogen bonding strength of a iodoloisoxazolium(III) salt - Reinhard, Dominik L.; Schmidt, Anna; Sons, Marc; Wolf, Julian; Engelage, Elric; Huber, Stefan M. (Beilstein Journal of Organic Chemistry, 2024)
Diaryliodonium(III) salts have been established as powerful halogen-bond donors in recent years. Herein, a new structural motif for this compound class was developed: iodoloisoxazolium salts, bearing a cyclic five-membered iodolium core fused with an isoxazole ring. A derivative of this class was synthesized and investigated in the solid state by X-ray crystallography. Finally, the potential as halogen-bonding activator was benchmarked in solution in the gold-catalyzed cyclization of a propargyl amide.
Keywords: diaryliodonium; gold catalysis; halogen bonding; hypervalent iodine; non-covalent interactions